Expression of visfatin in the diabetic rat retina. (19th February 2016) - Qu, Shen; Mo, Lijuan; Niu, Yunli; Sun, Xiaoting; Li, Houshuo; Wang, Zhen; Xu, Wei; Rong, Ao
Abstract: Background: Visfatin has been found in adipose tissue, liver and kidney of healthy and diabetic people, with its expression being increased in the aforementioned tissues in diabetes. Based on the former researches, visfatin may exist in the retina and affect the development of diabetic retinopathy. The expression of visfatin in Sprague–Dawley rats' retina, which may carve a path to study the pathogenesis of diabetic retinopathy, was investigated by this study. Methods: The mRNA and protein expression of visfatin in Sprague–Dawley rats' retina were detected by the reverse transcription‐polymerase chain reaction (RT‐PCR) and western blot. Immunohistochemical staining was applied to detect the expression location of visfatin in the rats' retinas. Results: The mRNA and visfatin protein expressions in both normal and streptozocin‐induced diabetic rats' retina increased significantly in 2 to 8 weeks of diabetes mellitus (DM). Compared with the normal control groups, the difference was statistically significant ( P < 0.05). The histological examination showed that the retinal thickness decreased gradually over the course of DM and the decrease in the outer nuclear layer was the most obvious. At 4 and 8 weeks, the decrease in the retinal thickness was significant ( P < 0.01). Visfatin was expressed in the retinal nerve fibre layer, inner plexiform layer and outer plexiform layer, and with the progression of DM, its expression was increased. Conclusions: Visfatin was expressed in the rats' retinas, mainly in the retinal nerve fibre layer, inner plexiform layer and outer plexiform layer. As the development of DM course, its expression was gradually increased.